Birthing ball therapy to reduce anxiety in mothers with induction of labor - Tias, Awit Rismaening; Mujahidah, Sa'adah; Hani, Umi; Mayangsari, Dewi (Link Journal of Mental Health, 2024)
Introduction: Anxiety and discomfort during labor represent the most intense experiences a woman has had in her lifetime. Anxiety in parturient women should be effectively mitigated since elevated anxiety can influence the perception of pain intensity. Anxiety and pain during labor might influence the progression and duration of labor. Methods to alleviate anxiety and labor pain encompass non-pharmacological treatments, such as birthing ball therapy, which can be implemented easily and effectively. A preliminary study conducted at Batang Hospital from May to June 2021 revealed that among 444 women in labor, 74.09% experienced spontaneous birth, 25.9% underwent cesarean section, and 34.7% had a prolonged initial stage of labor. Objectives: To assess the impact of birthing ball therapy on anxiety and labor pain in primiparous women undergoing induction. Methods: quasi-experimental with a pretest-posttest without a control group design. The sampling method employed was incidental sampling, with 23 respondents who met the inclusion criteria. Results: The Wilcoxon test yielded a p-value of 0.000, indicating a significant difference in anxiety levels and labor pain among first-time mums undergoing induction before and after birthing ball therapy. Conclusion: Birthing ball therapy influences anxiety and labor pain in first-time parturients undergoing induction at Batang Hospital.